1991
DOI: 10.1093/oxfordjournals.humrep.a137262
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic stem cell grafting: the therapy of the future?

Abstract: The grafting of mouse embryonic haemopoietic cells into deficient recipients is discussed. Donor cells can be obtained from post-implantation mouse embryos in vivo and used to treat X-irradiated or genetically anaemic recipients. The concept of grafting embryonic haemopoietic cells into normal, untreated recipients is also described. Preimplantation mouse blastocysts grown in vitro for 3-4 days can also be used as a source of donor cells. The haematological and immunological aspects of embryonic cell grafting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1992
1992
2009
2009

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…He reported functional colonization of the haematopoietic system of adult mice with cells from early post‐implantation mouse conceptuses or even blastocysts, regardless of whether they had been lethally irradiated (Hollands, 1987, 1988a, 1988b). He also found that such grafts could cure genetically anaemic mice (Hollands, 1988c), and worked xenogeneically between rat and mouse (reviewed in Hollands, 1991). In initial experiments, the donor material consisted of entire early post‐implantation stages within intact decidual tissue which is known to include cells originating from maternal bone marrow (Lysiak & Lala, 1992).…”
Section: Public Perceptionmentioning
confidence: 99%
“…He reported functional colonization of the haematopoietic system of adult mice with cells from early post‐implantation mouse conceptuses or even blastocysts, regardless of whether they had been lethally irradiated (Hollands, 1987, 1988a, 1988b). He also found that such grafts could cure genetically anaemic mice (Hollands, 1988c), and worked xenogeneically between rat and mouse (reviewed in Hollands, 1991). In initial experiments, the donor material consisted of entire early post‐implantation stages within intact decidual tissue which is known to include cells originating from maternal bone marrow (Lysiak & Lala, 1992).…”
Section: Public Perceptionmentioning
confidence: 99%